2009
DOI: 10.1007/s00382-009-0599-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of warm and cold situations in the Mediterranean basins on the West African monsoon: observed connection patterns (1979–2006) and climate simulations

Abstract: Using both empirical and numerical ensemble approaches this study focuses on the Mediterranean/West African relationship in northern summer. Statistical analyses utilize skin temperature, sea surface temperature, in situ and satellite rainfall, outgoing longwave radiation (OLR) observations and reanalyzed data winds and specific humidity on isobaric surfaces. Numerical investigations are based on a large set of sensitivity experiments performed on four atmospheric general circulation models (AGCM): ARPEGE-Clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
67
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 18 publications
16
67
0
Order By: Relevance
“…It is also known to exert a significant forcing on the African monsoon activity both on interannual and decadal scales, as reported in numerical experiments (Rowell, 2003;Fontaine et al, 2009).…”
Section: Mediterranean and Saharan Warmingmentioning
confidence: 83%
See 1 more Smart Citation
“…It is also known to exert a significant forcing on the African monsoon activity both on interannual and decadal scales, as reported in numerical experiments (Rowell, 2003;Fontaine et al, 2009).…”
Section: Mediterranean and Saharan Warmingmentioning
confidence: 83%
“…Briefly the cold and warm simulations correspond to a thermal forcing defined through observed SST canonical correlation analyses and only added over the Mediterranean: the boundary conditions over all other seas and oceans (Atlantic, Indian, Pacific Oceans) were the climatology observed. SST conditions have then been prescribed with these anomaly patterns added to the climatology of observed SST (Fontaine et al, 2009). Figure 15(a) and (b) presents the zonal and meridional mean moisture fluxes averaged between 20°W and 30°E in the low-and mid-tropospheric layers.…”
Section: Mediterranean and Saharan Warmingmentioning
confidence: 99%
“…The eastern Mediterranean region is a key region for tropical-extratropical interactions [Fontaine et al, 2010]. Sea surface temperatures and deep water formation in the eastern Mediterranean (EM) basin have an important role in preconditioning North Atlantic thermohaline circulation [Bethoux et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…In summer, it lies under the dominant influence of the subtropical desert belt, an area where the net fluxes of heat and moisture to the atmosphere result in a warm and salty sea surface layer [Bethoux et al, 1999]. Its thermal variability initiates a global atmospheric teleconnection that influences meridional overturning circulation, deep convection, and precipitation over the Sudan-Sahel region [Fontaine et al, 2010]. The Mediterranean Sea is also considered a sensitive region for climate forcing because of its size and limited exchange with the Atlantic Ocean [Bethoux et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…The SST in each basin, such as the Mediterranean Sea, Indian Ocean, and Atlantic Ocean, affects the inter-annual variability of the monsoon, whereas the global pattern affects the decadal variability Mohino et al, 2011;Losada et al, 2010a,b). Fontaine et al (2010) suggested that anomalously high Mediterranean SST leads to a strong West African monsoon. On the other hand, Bader and Latif (2003) suggested that anomalously high Indian Ocean SST correlates to less Sahel precipitation.…”
Section: Introductionmentioning
confidence: 99%